Grammar Learning Strategy (GLS): Male and Female EFL Students’ Preferences - Yuliana Yuliana; Heriyanti; Rinda Hardianti; Tsalisa Syifa Afia (Universitas Muhammadiyah Sorong, 2023)
This research compares the preference for Grammar Learning Strategies (GLS) between male and female EFL students of Universitas Muhammadiyah Sorong. The research aims to identify the preferred strategies for learning grammar among males and females students and determine if a statistically significant disparity exists in preference for grammar learning strategies among males and females students. A total of 70 students, comprising 35 males and 35 females, took part in the research. They were obtained from 48% of the entire population. A Simple Random Technique was employed to randomly select 35 males and 35 female students from all the classes. The data were gathered using Pawlak's Grammar Learning Strategy Inventory (GLSI) questionnaire. The acquired data were analyzed using the Independent sample t-test procedure using SPSS version 29. The results indicate that male students preferred social grammar learning strategies (GLS). The preference for cognitive grammar learning strategies (GLS) was found among female students, particularly for dealing with Corrective Feedback (CF). Male and female English as a Foreign Language (EFL) Students at Universitas Muhammadiyah Sorong did not differ significantly with regard to their preferred strategies for learning grammar. Based on the analysis of the data, the researchers found that there was no statistically significant distinction between males and females regarding the strategies they preferred to learn grammar. Both males and females are utilizing a Grammar Learning Strategy at a medium level.